Back cover: A new approach to detect a set of SNP‐SNP markers: Combining ARMS‐PCR with SNaPshot technology. Issue 13 (15th July 2020) - Zhang, Ranran; Tan, Yu; Jian, Hui; Qu, Shengqiu; Liu, Yuqing; Zhu, Jing; Wang, Li; Lv, Meili; Liao, Miao; Zhang, Lin; Yang, Fan; Liang, Weibo
Abstract : DOI: 10.1002/elps.202000009 The back cover picture shows two SNP loci linked tightly on a single chain, detected by ARMS‐PCR, combined with SNaPshot technology to obtain the haplotype of the SNP‐SNP. The 3′ end of ARMS primer is one of the alleles of SNP1, and the mismatch is introduced at the antepenult base. When the 3′ end was bound to SNP1, the mismatch had little effect on the primer binding ability, so the amplification product could be used as the template of SBE, and there was a corresponding electropherogram. When the 3′ end was not bound to SNP1, there was no electropherogram. That is, SNP1 can be typed according to the presence or absence of the target peak, and SNP2 can be typed according to the location and color of the target peak. The order of the covers online was updated December 23, 2020, after publication of the issue